Self-reported side effects following COVID-19 vaccination in athletes: A retrospective study - Klara Komici; Sofia Verderosa; Fabio D'Amico; Germano Guerra (Taylor & Francis Group, 2023)
Billions of coronavirus disease 19 (COVID-19) vaccines have been administered worldwide. However, limited data on side effects have been reported in athletes. This study aimed to describe the incidence of side effects following COVID-19 vaccination in athletes and to identify the factors associated with the main side effects in this population. Information on COVID-19 vaccination, side effects, and overall symptom duration was retrospectively collected from recreational and competitive athletes. A total of 460 participants were included in this study. Fever and arm pain were more frequently reported after the first-dose vaccination, 9.6% vs 4.6%, p = .007 and 81.3% vs 24.9%, p ≤ .001. Myalgia was more common after the second-dose vaccination, 0.65% vs. 7.1% p ≤ .001. Males were more likely to present with arm pain after the first and second vaccinations. Those with SARS-CoV-2 infection before vaccination were less likely to present with arm pain after the first dose of vaccination (OR: 0.162, p ≤ .001) and more likely to present with fever after the second dose of vaccination (OR: 3.442, p = .046). First-dose vaccination with the BNT162b2 vaccine compared to other brands was characterized by lower odds of fever (OR: 0.394, p = .017). Our results indicated mild adverse effects and a short duration of symptoms in athletes following COVID-19 vaccination.